Influence of repeated sprint exercise on leukocyte morphology in adolescent athletes at different biological maturation rates - Oliveira, Fernanda; Almeida-Neto, Paulo; Júnior, Geraldo Barroso Cavalcanti; Ururahy, Marcela Abbott Galvão; Dantas, Maria Angela; Cabral, Breno Guilherme De Araujo Tinoco; Dantas, Paulo Moreira Silva (Frontiers in Physiology, 2025)
BackgroundAfter performing strenuous physical exercises such as repeated sprint exercise (RSE), the leukocyte morphology undergoes changes suggesting immunodepression. Furthermore, it has been previously suggested that, in pediatrics, leukocyte changes may be influenced by the rates of the biological maturation (BM) process, which varies among individuals of similar chronological age.ObjectiveTo investigate the influence of RSE on leukocyte morphology in adolescent athletes at different rates of BM.MethodsWe conducted an experimental trial with a final sample consisting 21 adolescent athletes (male sex, age = 12.7 ± 1.2) underwent an RSE protocol, and blood samples were collected at “before, after, and 2 h post” moments. Based on the BM rates assessed by a predictive equation of skeletal age, participants were divided into two groups (Accelerated [n = 10] and Synchronized [n = 11]). Leukocyte morphology was analyzed microscopically and by leukogram.ResultsRegardless of the BM rates, a time effect was observed on the absolute levels of total leukocytes (g/L: η2p = 0.36), lymphocytes (g/L: η2p = 0.50, %: η2p = 0.29), segmented neutrophils (g/L: η2p = 0.16, %: η2p = 0.43), and neutrophil-to-lymphocyte ratio [NLR] (g/L: η2p = 0.30). The synchronized BM group showed higher values than the accelerated group for total leukocyte levels (moments after and 2 h post [η2p = 0.10; p < 0.001]) and segmented neutrophils (moments after and 2 h post [η2p = 0.10; p < 0.001]).ConclusionIn adolescent athletes, changes caused by RSE in leukocyte morphology appear to be dependent on the BM rates.